Tinea nigra Presenting Speckled or Salt and Pepper Pattern - Rossetto, Andre Luiz; Bella Cruz, Rosana Ce; Haddad Júnior, Vidal [UNESP] (Amer Soc Trop Med & Hygiene, 2014)
A 7-year-old Caucasian female resident of the southern coast of Brazil presented dark spots on the left palm that converged to a unique macule with speckled pattern at about 1 month. The mycological exam and the fungi culture were typical of Hortaea werneckii, the agent of the superficial mycosis Tinea nigra. The patient received butenafine hydrochloride 1% for 30 days, resulting in a complete remission of the lesion. At a follow-up visit 12 months after treatment, there was no lesion recurrence. We describe a form of rare geographical Tinea nigra with a speckled pattern. The salt and pepper aspect should be taken into consideration when the mycosis was suspected.